Efficacy and safety of vitamin-K antagonists and direct oral anticoagulants for stroke prevention in patients with heart failure and sinus rhythm: An updated systematic review and meta-analysis of randomized clinical trials. Issue 4 (April 2023) - Li, Weijia; Seo, Jiyoung; Kokkinidis, Damianos G; Palaiodimos, Leonidas; Nagraj, Sanjana; Korompoki, Eleni; Milionis, Haralambos; Doehner, Wolfram; Lip, Gregory Y. H.; Ntaios, George
Introduction: Heart failure (HF) is a major public health issue associated with significantly increased risk of stroke. It remains uncertain whether oral anticoagulation (OAC) in patients with heart failure and sinus rhythm (HF-SR) could improve prognosis. Methods: We performed a systematic search of PubMed and Embase databases for randomized controlled clinical trials assessing oral anticoagulants versus antiplatelets or placebo in patients with HF or ventricular dysfunction/cardiomyopathy without clinical HF and SR. The outcomes assessed were stroke/systemic embolism, major bleeding, myocardial infarction, all-cause mortality, and HF hospitalization. Results: Seven trials of 15, 794 patients were eligible for our analyses. The overall follow-up duration was 32, 367 patient-years corresponding to a mean follow-up of 2.05 years per patient. Four trials included patients treated with warfarin and three included patients treated with rivaroxaban. OAC was associated with reduced rate of stroke or systemic embolism compared to control (odds ratio (OR): 0.57, 95% confidence interval (CI): 0.44, 0.73, number needed to treat (NNT): 71.9) but higher rate of major bleeding (OR: 1.92, 95% CI: 1.47, 2.50, number needed to harm (NNH): 57.1). In the subgroup analysis according to the type of OAC, rivaroxaban was associated with significantly reduced rate of stroke or systemic embolism (1.24 vs 1.97 events per 100 patient-years, respectively, OR: 0.63, 95% CI: 0.45, 0.88, NNT: 82) and higher risk of major bleeding (OR: 1.66, 95% CI: 1.26, 2.20) compared to antiplatelets or placebo. There was no significant differences between groups for the outcomes of myocardial infarction, all-cause mortality, and HF hospitalization. Conclusion: This analysis shows that any benefit of OAC for stroke prevention may be offset by an increased risk of major bleeding in HF-SR patients. A well-designed randomized controlled trial of newer safer OACs is needed in this population.